Analisis Kendala Pendidik IPA Terhadap Pembelajaran IPA Terpadu - Bayu Priyatma; Darlen Sikumbang (Universitas Lampung, 2019)
This study aims to describe the constraints experienced by Science teachers in Private Middle School in Bandar Lampung in implementing Integrated Science learning. This study applied a qualitative research with research data that were closed questionnaires, semi-open questionnaires and interviews. The sample in this study consisted of all Science teachers in private schools which have already implemented the 2013 curriculum. The sampling technique was taken with total sampling technique. The results showed that the implementation of Integrated Science learning in the city of Bandar Lampung from three aspects of planning, implementation and learning assessment was classified under low constraints criteria. The main constraint in the planning aspect was the preparation of lesson plan, and the main constraint in the implementation aspect was the learning process on core activity indicators in the scientific approach and various learning methods on Integrated Science learning, while the constraints of the aspect of learning assessment included the assessment process in preparing assessment instruments.Penelitian ini bertujuan untuk mendeskripsikan kendala pendidik IPA di SMP Swasta Bandar Lampung dalam pelaksanaan pembelajaran IPA Terpadu. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan data penelitian berupa angket tertutup, angket semi terbuka dan wawancara. Sampel pada penelitian ini adalah seluruh pendidik IPA di sekolah yang sudah menerapkan Kurikulum 2013. Pengambilan sampel dilakukan dengan teknik total sampling. Hasil penelitian menunjukkan bahwa pelaksanaan pembelajaran IPA Terpadu di Kotamadya Bandar Lampung dari tiga aspek yaitu perencanaan, pelaksanaan dan penilaian pembelajaran, tergolong dalam kriteria kendala rendah. Kendala yang utama dalam aspek perencanaan adalah penyusunan RPP, kendala utama dalam aspek pelaksanaan pembelajaran pada indikator kegiatan inti dalam menerapkan pendekatan saintifik dan berbagai metode pembelajaran dalam proses pembelajaran IPA Terpadu dan aspek penilaian pembelajaran yaitu pada penilaian proses dalam menyusun instrumen penilaian.Kata kunci : kendala, pembelajaran IPA Terpadu, pendidik IPA